The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.clay.2018.07.043
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the structural changes of a pellet/powder bentonite mixture upon wetting by X-ray computed microtomography

Abstract: Pellet/powder bentonite mixture is one of the candidate materials for sealing plugs in deep geological high-level radioactive waste disposal. This note presents an investigation on the structure changes of this mixture occurring during the saturation process by means of X-ray computed micro-tomography. The test was performed in an infiltration column (60 mm in inner diameter and 120 mm in height). Water was supplied to the two ends of the column and the changes of the sample morphology were observed during a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…During hydration, the initially higher density of pellets decreases due to swelling and the initially lower density of powder increases due to soil compression and water content increase. [6] and [8] both noted that a pellet-powder mixture showed a relatively homogeneous structure even prior to full saturation, after several months of hydration. Figure 4 depicts the evolution of the transverse section of the sample during hydration obtained by X-ray computed microtomography.…”
Section: Evolution Upon Hydrationmentioning
confidence: 99%
See 4 more Smart Citations
“…During hydration, the initially higher density of pellets decreases due to swelling and the initially lower density of powder increases due to soil compression and water content increase. [6] and [8] both noted that a pellet-powder mixture showed a relatively homogeneous structure even prior to full saturation, after several months of hydration. Figure 4 depicts the evolution of the transverse section of the sample during hydration obtained by X-ray computed microtomography.…”
Section: Evolution Upon Hydrationmentioning
confidence: 99%
“…This results in a decreased inter-pellet void space and an increased interaggregate void space. While examining a pellet-powder bentonite mixture, [6] showed a downward movement of the powder, which was induced by gravity, towards large air-filled inter-pellet voids. It can be concluded that the larger peak of a PSD measured on a single pellet is influenced by the phenomena of cracking and crushing.…”
Section: Observed Behaviour Of Pellets and Pellet-based Materials 21mentioning
confidence: 99%
See 3 more Smart Citations